IMPROVING SENIOR HIGH SCHOOL STUDENTS’ SPEAKING ABILITY IN THE PROCESS OF LEARNING ENGLISH DISCUSSION USING TALKING CHIPS TECHNIQUE - Titin Nurjanah; Wida Widiastuti; Evi Kareviati (IKIP Siliwangi, 2019)
This research is a classroom action research. The objectives of this study were: (1) to find out whether there were significant differences in students' speaking abilities after being taught through Talking Chips techniques, and (2) to find out which techniques were better for improving students. 'Speaking ability. This research was conducted on second grade students at YAS Sindangkerta High School. The method used in this study is Class Action Research. The research was on two cycles with total meetings were seven; three meetings were for tests, and four meetings were for treatment. Each cycle covered the step of planning, acting, observing, and reflecting. The data were analyzed by using independent sample t-test in SPSS 16.0. There is a significant difference of the students’ speaking ability achievement between the students who were taught through the Talking Chips technique and taught without Talking Chips technique. In Cycle 1 the increase score 59.62 while in cycle 2 is 72.25. From the result of the data, teaching speaking through Talking Chips technique is more effective to increase students’ speaking ability because Talking Chips technique can give more enjoyable speaking atmosphere for students in the classroom. Keywords: Talking Chips, Speaking ,Car